2002
DOI: 10.1046/j.1365-2125.2002.01619.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tibolone in early and late postmenopausal women

Abstract: Aims Tibolone is a tissue-specific compound with favourable effects on bone, vagina, climacteric symptoms, mood and sexual well being in postmenopausal women, without stimulating the endometrium or breast. Since tibolone is used for the treatment of both young and elderly postmenopausal women, its pharmacokinetics were studied to investigate potential differences with age. In addition, the bioequivalence of the 1.25 and 2.5 mg tablets was evaluated. Methods Single doses of 1.25 or 2.5 mg of tibolone were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 9 publications
3
38
1
5
Order By: Relevance
“…However, AKR1C4 is exclusively expressed in the liver and predominantly catalyzes the formation of 3␣-hydroxytibolone. Therefore, these data may account for the fact that 3␤-hydroxytibolone is the major metabolite in tibolone target tissues and 3␣-hydroxytibolone is the major metabolite in the circulation (Blom, 2001;Timmer et al, 2002;Vos et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, AKR1C4 is exclusively expressed in the liver and predominantly catalyzes the formation of 3␣-hydroxytibolone. Therefore, these data may account for the fact that 3␤-hydroxytibolone is the major metabolite in tibolone target tissues and 3␣-hydroxytibolone is the major metabolite in the circulation (Blom, 2001;Timmer et al, 2002;Vos et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These reactions occur in the liver and intestine as well as in tibolone target tissues and are essential for 1) the apparent tissue-specific actions of tibolone (Kloosterboer and Ederveen, 2003) and 2) the catabolic clearance of the drug (Timmer et al, 2002;Vos et al, 2002). We previously demonstrated that the four human AKR1C isoforms catalyze the reduction of 5␣-DHT into 3␣-and 3␤-androstanediol (Steckelbroeck et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alcohols are more potent than parent at the estrogen receptor, while the alkene isomer is more potent at the androgen receptor (Escande et al, 2009). The 3a-hydroxy isomer is present at more than 9-fold greater concentrations than tibolone (Timmer et al, 2002) and thus can be estimated to have a 20-fold greater contribution than tibolone itself, assuming other distributional aspects are similar between parent and metabolite. The 3b isomer is also present at greater concentrations, but not as much as the other isomer.…”
Section: Procainamidementioning
confidence: 99%
“…The pharmacokinetics of tibolone in female patients have been studied recently, and the plasma concentrations of 3α-HMN and 3β-HMN were determined by using a gas chromatography-mass spectrometry (GC-MS) method [9] . However, the pharmacokinetics of tibolone metabolism in a Chinese human population have not been studied.…”
Section: Introductionmentioning
confidence: 99%